Institutionalizing OBE through Transformative Curriculum Management: Insights from an Indonesian Islamic University - Siti Romlah, Listiyani; Pahrudin, Agus; Fauzan, Ahmad; Kesuma, Guntur Cahya; Purnama, Rahmad (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study explores how Outcome-Based Education (OBE) is institutionalized. In the era of global educational reform and Industry 4.0, higher education institutions are required to adopt learning models that emphasize measurable competencies and graduate relevance to societal and industry needs. Outcome-Based Education (OBE) has emerged as a strategic response to these demands, particularly in Islamic higher education, where integration with spiritual and ethical values remains essential. This study aims to explore how OBE is institutionalized through transformative curriculum management at UIN Raden Intan Lampung, Indonesia, by analyzing its planning, implementation, and evaluation stages within the framework of Hunger and Wheelen’s strategic management theory. Using a qualitative approach with a case study method, data were collected through in-depth interviews, participant observation, and documentation review involving university leaders, curriculum developers, and lecturers. The findings reveal that the institutionalization of OBE at UIN RIL is characterized by a systematic and participatory process, including the formulation of learning outcomes aligned with the Indonesian National Qualifications Framework (KKNI), capacity building for lecturers, and the establishment of continuous quality improvement (CQI) mechanisms through internal audits and tracer studies. The study concludes that transformational leadership, adaptive governance, and integrated quality assurance systems are critical factors in sustaining OBE-based reforms. The implications of this research extend to other Islamic higher education institutions, offering a contextualized model of OBE integration that balances global educational standards with Islamic values and institutional identity. mative curriculum management at UIN Raden Intan Lampung. It examines the planning, implementation, and evaluation stages of curriculum management using Hunger and Wheelen’s strategic management theory. The qualitative approach and case study method were employed, involving curriculum developers, lecturers, and policymakers. Findings reveal a systematic transformation process involving stakeholder engagement, competency-based curriculum restructuring, and dynamic evaluation aligned with OBE principles. The study highlights the centrality of leadership, vision alignment, and adaptive governance in sustaining OBE-based reforms. These insights offer practical guidance for Islamic higher education institutions undergoing curriculum transformation.